2016
DOI: 10.1002/hyp.10959
|View full text |Cite
|
Sign up to set email alerts
|

Spatial characteristics and controlling factors of chemical weathering of loess in the dry season in the middle Loess Plateau, China

Abstract: Hydrochemistry methods were used to decipher the weathering and geochemical processes controlling solute acquisition of river waters in the dry season in the middle Loess Plateau (MLP), one of the most severely eroded areas and turbid riverine systems in the world. River waters were neutral to slightly alkaline with pH varying from 7.6 to 9.6. The total dissolved solids decreased from northwest to southeast with a mean value of 804 mg/l, much higher than the global average and other large rivers in China. Tern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 60 publications
3
32
0
Order By: Relevance
“…where ws is the water sample, atm is the atmospheric input, anth is the anthropogenic input, sil is silicate weathering, carb is carbonate weathering, and eva is evaporite dissolution. Detailed calculations for the forward modeling can be found in a previous study [4].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…where ws is the water sample, atm is the atmospheric input, anth is the anthropogenic input, sil is silicate weathering, carb is carbonate weathering, and eva is evaporite dissolution. Detailed calculations for the forward modeling can be found in a previous study [4].…”
Section: Discussionmentioning
confidence: 99%
“…For example, our previous study showed that over 30% of streamflow or groundwater samples from the Wei River had water quality of Class V in the wet season [15]; the Fen River had even worse water quality [16]. The dissolved solutes in this river mostly come from rock weathering, and the effect of human activities is different than that in other rivers [4]. Specifically, the Wei and Fen rivers support large areas of farmlands, a large population, and an industrial base, while the Hei River is much smaller, with anthropogenic inputs mostly from agriculture and coal mining.…”
Section: Implications For Water Resource Managementmentioning
confidence: 92%
See 3 more Smart Citations